2007
DOI: 10.1128/mcb.02339-06
|View full text |Cite
|
Sign up to set email alerts
|

A DOUBLETIME Kinase Binding Domain on the Drosophila PERIOD Protein Is Essential for Its Hyperphosphorylation, Transcriptional Repression, and Circadian Clock Function

Abstract: A common feature of animal circadian clocks is the progressive phosphorylation of PERIOD (PER) proteins from hypo-to hyperphosphorylated species, events that are highly dependent on casein kinase 1 (termed DOUBLETIME [DBT] in Drosophila melanogaster) and necessary for normal clock progression. Drosophila PER (dPER) functions in the negative limb of the clockworks by presumably binding to the transcription factor CLOCK (CLK) and inhibiting its transactivation activity. Here, we identify a small region on dPER t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
137
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(153 citation statements)
references
References 77 publications
16
137
0
Order By: Relevance
“…Because DBT controls the timing of PER's nuclear accumulation so that it does not occur until after the per/tim mRNA levels have peaked, molecular rhythms of per and tim mRNA are possible . Additional regulation has been proposed to occur at the level of PER's capacity to negatively regulate its transcription factor target (CLK/CYC) (Nawathean and Rosbash 2004;Kim and Edery 2006;Yu et al 2006;Kim et al 2007;Nawathean et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because DBT controls the timing of PER's nuclear accumulation so that it does not occur until after the per/tim mRNA levels have peaked, molecular rhythms of per and tim mRNA are possible . Additional regulation has been proposed to occur at the level of PER's capacity to negatively regulate its transcription factor target (CLK/CYC) (Nawathean and Rosbash 2004;Kim and Edery 2006;Yu et al 2006;Kim et al 2007;Nawathean et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was first shown that PER was rhythmically phosphorylated (Edery et al 1994), and isolation and analysis of the dbt mutants in Drosophila then showed that casein kinase I (CKI) targets PER for phosphorylation and degradation Price et al 1998;Rothenfluh et al 2000a;Suri et al 2000;Muskus et al 2007). Doubletime (DBT) has also been proposed to regulate the nuclear localization (Bao et al 2001;Cyran et al 2005;Nawathean et al 2007) and the repressor capacity of PER (Nawathean and Rosbash 2004;Kim et al 2007;Nawathean et al 2007), as well as the phosphorylation of CLK protein (Kim and Edery 2006;Yu et al 2006). In addition, two other kinases [casein kinase II, CKII (Lin et al 2002) and SGG (Martinek et al 2001)] and two protein phosphatases [PP2A (Sathyanarayanan et al 2004;Fang et al 2007) and PP1 (Fang et al 2007)] contribute to rhythmic phosphorylation of clock proteins.…”
mentioning
confidence: 99%
“…During this time, PER and TIM progressively associate in distinct foci, which are lost as PER and TIM dissociate and move to the nucleus. In the nucleus, PER, DBT, and possibly TIM, associate with Clock/Cycle complexes, inhibiting transcription of Clock/cycle-dependent genes including per and tim (see also Kim et al 2007;Nawathean et al 2007). The duration of the PER/TIM complex in the cytoplasm is affected by PER L which delays the onset of nuclear accumulation by about 3 hours.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Drosophila PER has been proposed to inhibit circadian transcription by recruiting kinases to the CLK/CYC complex Kim et al 2007). Consistent with this view, a recent failure to detect an association of wildtype PER with DNA by chromatin immunoprecipitation (ChIP) was interpreted to suggest that PER normally promotes phosphorylation by interacting only transiently with chromatin-bound CLK (Yu et al 2009).…”
mentioning
confidence: 96%